Os impactos na arrecadação do ICMS-CE do setor de material de construção, ferragens e ferramentas, após a implementação do regime de arrecadação por substituição tributária - Pereira, Carlos Rogério dos Santos (2017)
The objective of this dissertation is to analyze the effects on the collection of ICMS in the sector of construction materials, ironmongery and tools in the State of Ceará after the implementation of the regime of tax substitution by net load, regulated by Decree No. 31,270, of August 1 of 2013. For that, an econometric model of multiple regression estimated by Least Squares Generalized using the Prais-Winsten methodology was specified, where the dependent variable was the total monthly ICMS collection of the companies of the industrial sector and wholesaler of the Decree n ° 31.270/2013. The exogenous variables were corporate income, the basic interest rate (Selic), the percentage of employees and unemployed persons of the General Register of Employed and Unemployed (CAGED), as well as variables to measure the growth trend of the collection and the seasonalities from the series. In addition, a dummy variable was included in order to verify the effects on ICMS tax collection after the change to the tax substitution regime. Thus, the estimated results showed that, after the date of the commencement of Decree No. 31.270/2013, ICMS collected in the Wholesale and Industry sectors increased in level. However, after that same date, the statistical evidence indicates that its long-term trajectories were decreasing after the beginning of this decree.